Energy efficiency on the reefer container storage yard: An analysis of thermal performance of installation roof shade - Muhammad Arif Budiyanto; Takeshi Shinoda (Energy Reports, 2020)
This study aims to estimate the effect of energy efficiency by installing roof shade in the reefer container storage. A cross sectional of reefer container was simulated by using thermal simulation to investigate thermal performance and estimate the energy efficiency. The roof shade is used to reducing heat penetration on the container surface caused by strong load of solar radiation during the day. Since the thermal performance is difficult to estimate on measurement experiment because the effects are not always so much and have strong deviation, thermal simulation provides a useful tool to predict the temperature distribution. The current thermal simulation model consists of thermal radiation and conjugate heat transfer. Measurement of solar radiation was carried out to provide thermal boundary condition and temperature measurement was carried out to validate the simulation model. The simulation result confirms 9% energy efficiency by installation of roof shade during the day.
Keywords: 330; Reefer container; Container yard; Roof shade; Thermal simulation